The role of a public university in a global environment: Networks and externalities of the R&D of the Cauca University (2013)
This article analyzes indicators of science and technology, showing the participation of the University of Cauca in the generation of network externalities. The methodology addresses quantitative and qualitative designs. Consists of a descriptive study that covers the main indicators of R&D and network externalities from the view of the specialized literature, and an analytical study that uses the technique known as method of consensus panel of experts. The answers of the experts are processed to determine the level of consistency and identify indicators of R&D that facilitate the measurement of network externalities, such as the production of new knowledge‐related products; number of networks through programs of postgraduates in national conventions; and number of graduates in specializations, master's and doctoral programs.